Batik Jlamprang Wujud Dari Warisan Budaya Kota Pekalongan - Bariroh, Bariroh; Naam, Muh Fakhrihun; Sugiarto, Eko (Jurnal Ilmu Sosial, Humaniora dan Seni, 2024)
Jlamprang batik is a form of cultural heritage originating from the city of Pekalongan, Central Java. Known for its distinctive geometric motifs and use of bright colours, this batik not only displays visual beauty but also contains deep philosophical meanings. This article discusses the history, uniqueness of the motif, and values contained in Jlamprang batik. Jlamprang batik serves not only as an artistic and economic product but also as a guardian of the cultural and historical identity of Pekalongan city, as well as a reflection of the richness and diversity of Indonesian culture. This research aims to explore Jlamprang batik as a form of Pekalongan's cultural heritage using qualitative research methods. Through interviews with an employee of the Pekalongan Batik Museum and literature studies through literature searches in the form of journals related to Jlamprang batik. This research reveals the history, uses, and philosophical meanings contained in Jlamprang batik. The results show that Jlamprang batik, with its geometric motifs and bright colours, reflects not only artistic beauty but also the cultural and spiritual values of the Pekalongan people.